Geographic Variation in Signal Preferences in the Tropical Katydid Neoconocephalus triops - Oliver M. Beckers; Johannes Schul (Biology)
In communication systems, the signal and preference for the signal have to match, limiting phenotypic variation. Yet, communication systems evolve, but the mechanisms of how phenotypic variation can come into existence while not disrupting the match are poorly understood. Geographic variation in communication can provide insights into the diversification of these systems. Females of the katydid Neoconocephalus triops use the pulse rate and call structure for call recognition. Using behavioral experiments, we determined preferences for pulse rate at two relevant ambient temperatures and preferences for call structure (continuous, versed) in females from Puerto Rico and Costa Rica. Puerto Rican females had closed preference at both tested temperatures, indicating high selectivity for pulse rate. In contrast, Costa Rican females had a closed preference only at 20 °C; at 25 °C the females were unselective toward higher than natural pulse rates. Additionally, Puerto Rican females were not selective for call structure, whereas Costa Rican females preferred versed calls. It is not clear whether the differences in pulse preference were due to neural constraints or different selective pressures, however, they may facilitate further divergence and reproductive isolation. Importantly, the reduced selectivity for call structure or pulse rate allows calls to display the necessary variation for the communication system to evolve.